Penerapan Model Pembelajaran Discovery Learning Berbantuan GeoGebra untuk Meningkatkan Hasil Belajar Materi Fungsi Kuadrat - Sholekah, Iis; Andaini, Susy Kuspambudi; Rofiki, Imam (Universitas Negeri Surabaya, 2025)
Quadratic function is important for students to understand because they are useful for everyday life. In reality, most students still face difficulties in solving quadratic function problems. Meanwhile, quadratic function material is needed to understand subsequent material topics such as integrals, derivatives and linear programming. Apart from that, the results of observations on quadratic function material, students do not understand the visualization of quadratic function graphs and students tend to memorize formulas so that when faced with a problem, students forget which formula to use. The application of discovery learning combined with the use of GeoGebra has the potential to stimulate student understanding so that it has a positive effect on learning outcomes. Therefore, the aim of this research is to implementation discovery learning model assisted by GeoGebra to find out actions that can improve learning outcomes. This research uses Classroom Action Research (PTK) guided by the Mc. Taggart and Kemmis design with research stages which include planning, action, observation, and reflection. The subjects in this research consisted of 35 students from class X-K MAN 1 Trenggalek. Data is obtained by observing and administering tests at the end of each cycle. The research results reported that the average value of student learning outcomes after participating in Cycle I learning activities was 67.13 and 74.64 after participating in Cycle II learning activities. Apart from that, the results obtained in Cycle I of student learning completion were 65.71% and in Cycle II it was 77.14%. Student learning outcomes on the topic of quadratic functions can be improved through learning that applies discovery learning assisted by GeoGebra.